2012
DOI: 10.1152/ajpcell.00327.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tonicity-independent regulation of the osmosensitive transcription factor TonEBP (NFAT5)

Abstract: Tonicity-responsive enhancer binding protein (TonEBP/nuclear factor of activated T-cells 5 [NFAT5]) is a Rel homology transcription factor classically known for its osmosensitive role in regulating cellular homeostasis during states of hypo- and hypertonic stress. A recently growing body of research indicates that TonEBP is not solely regulated by tonicity, but that it can be stimulated by various tonicity-independent mechanisms in both hypertonic and isotonic tissues. Physiological and pathophysiological stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 78 publications
2
92
1
1
Order By: Relevance
“…TonEBP also participates in compatible osmolyte accumulation by upregulating relevant genes (Coleman et al, 2000;Miyakawa et al, 1998;Rim et al, 1998). The DNA sequence of the TonEBP binding site in the AQP2 promoter is GGAAA (Halterman et al, 2012); the bottlenose dolphin AQP2 proximal promoter includes this sequence at −139 and −327 bp upstream of the start codon (turTru1: GeneScaffold_1570, Ensembl Genome Blowser). The TonEBP gene is present in the bottlenose dolphin (ENSTTRG00000010017), and we confirmed that TonEBP mRNA is expressed and upregulated by addition of NaCl in dolphin renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…TonEBP also participates in compatible osmolyte accumulation by upregulating relevant genes (Coleman et al, 2000;Miyakawa et al, 1998;Rim et al, 1998). The DNA sequence of the TonEBP binding site in the AQP2 promoter is GGAAA (Halterman et al, 2012); the bottlenose dolphin AQP2 proximal promoter includes this sequence at −139 and −327 bp upstream of the start codon (turTru1: GeneScaffold_1570, Ensembl Genome Blowser). The TonEBP gene is present in the bottlenose dolphin (ENSTTRG00000010017), and we confirmed that TonEBP mRNA is expressed and upregulated by addition of NaCl in dolphin renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Could it be that this NFAT5 regulation of CACNA1C is important throughout the life of the organism? As we found above, the signals to activate NFAT5 are many; the first found was an osmotic stimulus [2,4]. A critical question is, "what drives the mechanisms of activation here?"…”
mentioning
confidence: 87%
“…Hypertonicity activates NFAT5 by increasing its nuclear localization and by transactivating its activity in the early phase and protein abundance in the late phase of activation. The inhibition of NFAT5 by hypotonicity features a decrease in nuclear NFAT5 expression.Recent evidence indicates that NFAT5 is not solely regulated by tonicity, but instead that NFAT5 can be stimulated by various tonicity-independent mechanisms in both hypertonic and isotonic tissues [4]. Cytokines, growth factors, receptor and integrin activation, contractile agonists, ions, and reactive oxygen species have all been implicated in the positive regulation of NFAT5 expression and activity in diverse cell types, notably immune cells [5].…”
mentioning
confidence: 99%
“…FSP27-k NFAT5 (nuclear factor of activated T cells 5; aktibatutako T zelulen faktore nuklearra 5) transkripzio-faktorea bahitzen du, eta nukleora sartzea oztopatuz bere jarduera murrizten du [23]. NFAT5 transkripzio-faktoreak estres hipertonikoari eta estimulu ugariri aurre egiteko erregulatzen du gene-adierazpena [24,25] eta, beraz, LTek homeostasiaren modulazioan dihardutela esan daiteke.…”
Section: Zitosoleko Lipido-tanten Sorrera Eta Erabileraunclassified